Nitrogen-doped carbon onion nanotube chain absorbing material and its preparation method and application

Through a simple method, nitrogen-doped carbon onion nanotube chain absorption materials are prepared, which solves the problems of high preparation cost and difficulty in regulation of carbon-based microwave absorption materials, and achieves high-efficiency and low-cost absorption performance improvement, meeting industrial needs .

CN116873906BActive Publication Date: 2024-12-31PANZHIHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311011057.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-11
Publication Date
2024-12-31
Estimated Expiration
2043-08-11

AI Technical Summary

Technical Problem

The preparation cost of existing carbon-based microwave absorbing materials is high and difficult to finely regulate, and cannot meet industrial needs and upgrades.

Method used

A simple method is used to prepare nitrogen-doped carbon onion nanotube chain absorbing material. By heat treatment of the carbon onion nanotube chain and the nitrogen source under a protective atmosphere, a material with excellent absorbing properties is prepared.

Benefits of technology

It realizes low-cost, efficient preparation and fine control of structural size. The obtained nitrogen-doped carbon onion nanotube chain absorbing material has an effective absorption bandwidth of 3.3GHz when the thickness is 1.3mm, and the minimum reflection loss is -45.58dB, with excellent performance. in traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116873906B_ABST
    Figure CN116873906B_ABST
Patent Text Reader

Abstract

The present invention provides a nitrogen-doped carbon onion nanotube chain absorbing material and a preparation method and application thereof, and belongs to the field of lightweight microwave absorbing materials. The preparation method of the present invention comprises: (1) preparing a carbon onion nanotube chain: using a candle as a raw material, after lighting it, placing a plate at the outer flame of the flame, forming a carbon layer on the surface of the plate, and collecting the carbon layer, namely the carbon onion nanotube chain; (2) preparing a nitrogen-doped carbon onion nanotube chain absorbing material: after the carbon onion nanotube chain prepared in step (1) is uniformly mixed with a nitrogen source, heat-treated at 350-400°C for 2-4h under a protective atmosphere, a nitrogen-doped carbon onion nanotube chain absorbing material is obtained. The method is low in cost and simple in steps, and the prepared nitrogen-doped carbon onion nanotube chain absorbing material has excellent absorbing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of lightweight microwave absorbing materials, and in particular to a nitrogen-doped carbon onion nanotube chain absorbing material and a preparation method and application thereof. Background Art

[0002] At present, electromagnetic waves play an important role in the era of intelligence, such as 5G communications, biomedicine, and defense and military fields. However, while it brings convenience to people's lives, it also generates a lot of electromagnetic pollution. Electromagnetic pollution not only poses a hazard to human health, but also threatens the normal operation of precision equipment. So far, there are two common strategies for preventing electromagnetic pollution, namely shielding and absorption. Compared with the traditional shielding strategy based on the reflection principle, absorbing materials can sustainably convert electromagnetic waves into heat energy or other forms of energy dissipation, which has attracted the attention and pursuit of many researchers. Generally, ideal microwave absorbing materials should be thin, light, wide bandwidth and strong absorption. Therefore, carbon-based materials have the characteristics of light weight, large specific surface area, strong electromagnetic wave attenuation ability and good environmental stability, and have broad application prospects in the field of microwave absorption.

[0003] Graphene, carbon black, carbon nanotubes and porous carbon are typical representatives of carbon-based materials that have attracted much attention. For example, Wang et al. successfully synthesized a three-dimensional porous CFO / N-rGO composite structure by embedding CoFe2O4 (CFO) nanoparticles in N-doped reduced graphene oxide aerogels through a simple solvothermal method and freeze-drying technology. The electromagnetic properties of CFO / N-rGO aerogels were optimized by adjusting the amount of CFO nanoparticles added. When the mass ratio of GO to CFO is 1:2, the microwave absorption performance is optimal. When the thickness is 2.1 mm and the CFO / N-rGO loading rate is 20wt%, the minimum reflection loss (RLmin) at 14.4GHz reaches -60.4dB. In addition, when the thickness is 2.2 mm, its effective absorption bandwidth (RL<-10dB) can reach 6.48GHz (11.44-17.92GHz). PHe used a solvent-free mechanochemical method to prepare a core-shell carbon black@ACR nanocomposite with acrylic resin (ACR) as a matching layer for carbon black. After the introduction of the ACR core-shell structure, the RL value of the carbon black@ACR composite material reached a minimum value of -48.3dB at 11.7GHz when the thickness was 2.4 mm, and the effective absorption bandwidth (RL<-10dB) reached 5.86GHz (12.14GHz-18GHz) when the thickness was 2 mm. Compared with carbon black, the minimum reflection loss increased by about 160%, and the widest effective absorption bandwidth was widened by about 642%. At the same time, the thickness of the material was thinner than the original carbon black, achieving the effect of "stronger, wider, and thinner". D Liu et al. successfully prepared carbon nanotubes@nickel / carbon foams (CNCFs) through a two-step pyrolysis process. When the relative carbon content in CNCFs was 66.3wt%, it showed amazing microwave absorption performance. When the absorber thickness is 1.8mm, the effective absorption bandwidth of CNCFs reaches 5.8GHz, and the minimum reflection loss intensity is -47.0dB. J Tao prepared multi-shell hollow porous carbon nanoparticles (HPCNs) by a simple liquid phase method combined with a layer-by-layer process. The use of a multi-shell structure helps to improve the conduction loss and polarization loss of the matrix, thereby improving the microwave absorption performance of the sample. At a thickness of 1.6mm, the three-shell HPCNs composite material has an effective absorption bandwidth (EAB) of 5.17GHz and an optimal reflection loss (RL) of -18.13dB at 14.66GHz. Despite this, there are still some limitations to the widespread application of carbon-based structures in the field of microwave absorbing materials. These limitations are mainly manifested in three aspects: first, the time-consuming and complex preparation scheme leads to a high production cost of carbon-based structures; second, the precursors required to prepare carbon-based structures are expensive and may bring secondary harm to the environment and society; third, the geometric structure and size of carbon-based materials are difficult to accurately adjust and optimize. It can be seen that lightweight carbon-based microwave absorbing materials with high production costs and difficulty in fine-tuning control cannot effectively meet the growing demand for industrialization and upgrading.Therefore, it remains a difficult problem to achieve efficient preparation of carbon-based absorbing materials and fine control of their structural dimensions based on a low-cost and simple strategy. Summary of the invention

[0004] In view of the above problems or deficiencies, in order to solve the problem that the prior art is difficult to achieve efficient preparation of carbon-based absorbing materials and fine control of microstructures, the present invention provides nitrogen-doped carbon onion nanotube chain absorbing materials and preparation methods and applications thereof. The preparation method is simple, low-cost, and can achieve fine control of the size and structure of carbon materials.

[0005] The technical solution of the present invention is as follows:

[0006] The present invention provides a method for preparing a nitrogen-doped carbon onion nanotube chain absorbing material, comprising the following steps:

[0007] (1) Preparation of carbon onion nanotube chains: A candle is used as a raw material, and after it is ignited, a plate is placed outside the flame of the flame to form a carbon layer on the surface of the plate, and the carbon layer is collected to obtain a carbon onion nanotube chain;

[0008] (2) Preparation of nitrogen-doped carbon onion nanotube chain absorbing material: After uniformly mixing the carbon onion nanotube chain prepared in step (1) with a nitrogen source, heat-treating at 350-400° C. for 2-4 h under a protective atmosphere to obtain a nitrogen-doped carbon onion nanotube chain absorbing material.

[0009] In a specific embodiment of the present invention, the surface of the plate is smooth; preferably, the plate is any one of a glass sheet, a silicon sheet, and an aluminum sheet.

[0010] In a specific embodiment of the present invention, the plate is placed at 0.5-1 cm from the flame.

[0011] In a specific embodiment of the present invention, the carbon onion nanotube chain has a chain length of 200-400 nm and a tube diameter of 20-50 nm.

[0012] In a specific embodiment of the present invention, the nitrogen source is at least one of ammonium chloride, ammonium nitrate, ammonium sulfate and urea; preferably, the nitrogen source is ammonium chloride.

[0013] In a specific embodiment of the present invention, in step (2), the ratio of carbon onion nanotube chain to nitrogen source is 1-3:2.62-5.24.

[0014] In a specific embodiment of the present invention, in step (2), the nitrogen source is ammonium chloride, and the mass ratio of carbon onion nanotube chain to ammonium chloride is (1-3):(10-20); preferably, the mass ratio of carbon onion nanotube chain to ammonium chloride is 1:10.

[0015] The present invention provides a nitrogen-doped carbon onion nanotube chain absorbing material prepared by the preparation method of the nitrogen-doped carbon onion nanotube chain absorbing material.

[0016] The present invention also provides application of nitrogen-doped carbon onion nanotube chain wave absorbing material in electromagnetic wave absorption.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The preparation method of the present invention has low cost and simple steps, and the prepared nitrogen-doped carbon onion nanotube chain absorbing material has excellent absorbing performance: it contains a nitrogen-doped carbon onion nanotube chain composite material with a mass fraction of 50%. When the thickness is 1.3 mm, the effective absorption bandwidth is 3.3 GHz (reflection loss value is less than -10 dB), and the minimum reflection loss is -45.58 dB (16.95 GHz). BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 XRD diffraction patterns of the materials prepared in Examples 1-4;

[0020] Figure 2 The scanning electron microscope images of the materials prepared in Examples 1-4;

[0021] Figure 3 Transmission electron microscope images of the materials prepared in Example 1, Example 3, and Example 4;

[0022] Figure 4 XPS graphs of the materials prepared in Examples 1-4;

[0023] Figure 5 The dielectric constants of the materials prepared in Examples 1-4, wherein (a) the real part; (b) the imaginary part;

[0024] Figure 6 Reflection loss curve of a composite material prepared by uniformly mixing the material prepared in Example 1-4 with paraffin in a mass ratio of 1:1 (thickness 1.3 mm). DETAILED DESCRIPTION

[0025] The present invention provides a method for preparing a nitrogen-doped carbon onion nanotube chain absorbing material, comprising the following steps:

[0026] (1) Preparation of carbon onion nanotube chains: A candle is used as a raw material, and after it is ignited, a plate is placed outside the flame of the flame to form a carbon layer on the surface of the plate, and the carbon layer is collected to obtain a carbon onion nanotube chain;

[0027] (2) Preparation of nitrogen-doped carbon onion nanotube chain absorbing material: After uniformly mixing the carbon onion nanotube chain prepared in step (1) with a nitrogen source, heat-treating at 350-400° C. for 2-4 h under a protective atmosphere to obtain a nitrogen-doped carbon onion nanotube chain absorbing material.

[0028] When a candle burns, the flame core mainly produces diamond carbon, which has very low conductivity and is not suitable as an absorbing material.

[0029] The temperature of heat treatment of carbon onion nanotube chain and nitrogen source directly affects the dielectric constant and nitrogen content of nitrogen-doped carbon onion nanotube chain absorbing material. When the heat treatment temperature is lower than 350℃, the dielectric constant increases significantly, that is, the conductivity increases. For absorbing materials, higher conductivity means that the impedance matching between the absorbing structure and the free space becomes worse. When electromagnetic waves pass through the absorbing material, more electromagnetic waves are reflected rather than absorbed, and the absorbing performance is poor. When the heat treatment temperature is higher than 400℃, the nitrogen content of nitrogen-doped carbon onion nanotube chain absorbing material decreases, the CN heterostructure decreases, the dipole polarization and interface polarization are weakened, and the absorbing performance decreases.

[0030] In the present invention, the protective atmosphere is an atmosphere that does not participate in the reaction, including but not limited to nitrogen atmosphere, helium atmosphere, argon atmosphere, neon atmosphere, krypton atmosphere, etc.

[0031] In a specific embodiment of the present invention, the surface of the plate is smooth; preferably, the plate is any one of a glass sheet, a silicon sheet, and an aluminum sheet.

[0032] In the present invention, the plate material is not limited to glass plate, silicon plate, aluminum plate, and any plate material can be used as long as it is a temperature-resistant plate material.

[0033] In a specific embodiment of the present invention, the plate is placed at 0.5-1 cm from the flame.

[0034] In a specific embodiment of the present invention, the carbon onion nanotube chain has a chain length of 200-400 nm and a tube diameter of 20-50 nm.

[0035] In a specific embodiment of the present invention, the nitrogen source is at least one of ammonium chloride, ammonium nitrate, ammonium sulfate and urea; preferably, the nitrogen source is ammonium chloride.

[0036] In a specific embodiment of the present invention, in step (2), the mass ratio of carbon onion nanotube chain to nitrogen source is 1-3:2.62-5.24.

[0037] As a good absorbing material, it needs appropriate conductivity. If the nitriding amount is too high, most of the CC bonds will be converted into CN bonds, which will make the material conductivity lower. Although the impedance matching is optimized to a certain extent, it will reduce and weaken the material's loss capacity for electromagnetic waves, thereby reducing the absorbing ability. If the nitriding amount is small, this will make the material conductivity higher. Although the material maintains a strong loss capacity, its impedance matching with free space becomes worse, resulting in reflection when electromagnetic waves pass through the material, and thus the electromagnetic waves cannot be lost. Therefore, controlling the nitriding amount within a suitable range can not only maintain the material's loss capacity for electromagnetic waves, but also optimize impedance matching. During the nitriding process, the mass ratio of the carbon onion nanotube chain to the nitrogen source is controlled at 1-3:2.62-5.24, which can satisfy the nitriding amount of the nitrogen-doped carbon onion nanotube chain absorbing material to be controlled within a suitable range.

[0038] In a specific embodiment of the present invention, in step (2), the nitrogen source is ammonium chloride, and the mass ratio of carbon onion nanotube chain to ammonium chloride is (1-3):(10-20); preferably, the mass ratio of carbon onion nanotube chain to ammonium chloride is 1:10.

[0039] The present invention provides a nitrogen-doped carbon onion nanotube chain absorbing material prepared by the preparation method of the nitrogen-doped carbon onion nanotube chain absorbing material.

[0040] The present invention also provides application of nitrogen-doped carbon onion nanotube chain wave absorbing material in electromagnetic wave absorption.

[0041] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0042] Example 1

[0043] The method for preparing a carbon onion nanotube chain comprises the following steps:

[0044] A discarded candle is selected, and after the candle is lit, a piece of smooth glass is placed 0.5-1 cm away from the flame. After keeping it for 3-5 minutes, a carbon layer with a thickness of 50nm-100nm is formed on the glass surface. The carbon layer is collected, which is the carbon onion nanotube chain, recorded as CONC.

[0045] Example 2

[0046] The preparation method of nitrogen-doped carbon onion nanotube chain wave absorbing material comprises the following steps:

[0047] The carbon onion nanotube chain (CONC) prepared in Example 1 was uniformly mixed with ammonium chloride in a mass ratio of 1:10, placed in a tube furnace, and annealed in an argon atmosphere to obtain a nitrogen-doped carbon onion nanotube chain, denoted as NCONC-300; wherein the annealing temperature was 300°C and the time was 3h.

[0048] Example 3

[0049] The preparation method of nitrogen-doped carbon onion nanotube chain wave absorbing material comprises the following steps:

[0050] The carbon onion nanotube chain (CONC) prepared in Example 1 was uniformly mixed with ammonium chloride in a mass ratio of 1:10, placed in a tube furnace, and annealed in an argon atmosphere to obtain a nitrogen-doped carbon onion nanotube chain, denoted as NCONC-350; the annealing temperature was 350°C, and the time was 3h.

[0051] Example 4

[0052] The preparation method of nitrogen-doped carbon onion nanotube chain wave absorbing material comprises the following steps:

[0053] The carbon onion nanotube chain (CONC) prepared in Example 1 was uniformly mixed with ammonium chloride in a mass ratio of 1:10, placed in a tube furnace, and annealed in an argon atmosphere to obtain a nitrogen-doped carbon onion nanotube chain, denoted as NCONC-400; the annealing temperature was 400°C and the time was 3h.

[0054] X-ray diffraction was performed on CONC, NCONC-300, NCONC-350 and NCONC-400 prepared in Examples 1-4 to obtain XRD patterns. Figure 1 As shown. Figure 1 It can be seen that the main components of NCONC-300, NCONC-350 and NCONC-400 are carbon onion nanotube chains (CONC).

[0055] The CONC, NCONC-300, NCONC-350 and NCONC-400 prepared in Examples 1-4 were subjected to scanning electron microscopy (SEM) analysis to obtain SEM images, see Figure 2 As shown. Figure 2 It can be seen that the surface morphology of CONC, NCONC-300, NCONC-350 and NCONC-400 has no significant change.

[0056] CONC, NCONC-350 and NCONC-400 prepared in Example 1, Example 3 and Example 4 were analyzed by transmission electron microscopy (TEM) to obtain TEM images. Figure 3As shown, Figures (a), (b), and (c) are TEM images of CONC; Figures (d), (e), and (f) are TEM images of NCONC-350; Figures (g), (h), and (i) are TEM images of NCONC-400. Figure 3 It can be seen that the single chain length of CONC is about 300nm, the tube diameter is 22nm, and its elemental analysis results show that its main components are C and O elements. The TEM images of NCONC-350 and NCONC-400 show that the N element is successfully doped. And with the increase of heat treatment temperature, the lattice ordering degree of nitrogen-doped carbon onion nanotube chains changes significantly. When the heat treatment temperature is 400℃, the lattice fringes are more obvious and the degree of ordering is significantly improved.

[0057] X-ray photoelectron spectroscopy (XPS) analysis was performed on CONC, NCONC-300, NCONC-350 and NCONC-400 prepared in Examples 1-4. Figure 4 As shown. Figure 4 It can be seen that the N element in Example 2-4 was successfully doped therein.

[0058] The dielectric constants of CONC, NCONC-300, NCONC-350 and NCONC-400 prepared in Examples 1-4 were measured, and dielectric constant curves were plotted. Figure 5 As shown, (a) real part; (b) imaginary part. Figure 5 (a) It can be seen that after nitriding at 300℃, the real and imaginary parts of the dielectric constant are significantly increased compared with CONC. However, after nitriding at 350℃ and 400℃, the real and imaginary parts of the dielectric constant are significantly reduced compared with CONC.

[0059] CONC, NCONC-300, NCONC-350 and NCONC-400 prepared in Examples 1-4 were uniformly mixed with paraffin wax at a mass ratio of 1:1 to prepare composite materials (thickness of 1.3 mm). The reflection loss curves (RL curves) of the four composite materials are shown in FIG. Figure 6 As shown. Figure 6It can be seen that at a thickness of 1.3mm, the absorption bandwidth of CONC is 2.84GHz (12.80GHz-15.64GHz), and the minimum reflection loss value is -11.84dB (14.06GHz). The effective absorption bandwidth of NCONC-300 is 0GHz, and the minimum reflection loss value is -9.39dB (12.39GHz). The minimum reflection loss of NCONC-350 is -45.58dB (16.95GHz), and the effective absorption bandwidth is 3.30GHz (14.70GHz-18.0GHz). The minimum reflection loss value of NCONC-400 is -26.69dB (16.50GHz), and the effective absorption bandwidth is 3.74GHz (14.16GHz-18GHz).

[0060] In summary, after nitriding at 300℃, the dielectric constant of CONC increases significantly, which means that the conductivity increases. For absorbing materials, higher conductivity means that the impedance matching between the absorbing structure and the free space becomes worse. When electromagnetic waves pass through the absorbing material, more electromagnetic waves are reflected rather than absorbed. Therefore, its absorbing performance and bandwidth are lower than those of CONC. After nitriding at 350℃ and 400℃, the dielectric constant of CONC decreases significantly, the impedance matching improves significantly, and the absorbing performance and bandwidth increase significantly compared with CONC.

[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a nitrogen-doped carbon onion nanotube chain absorbing material, characterized in that: The steps include: (1) Preparation of carbon onion nanotube chains: Using a candle as a raw material, after lighting it, placing a plate 0.5-1 cm away from the flame, forming a carbon layer on the surface of the plate, and collecting the carbon layer, which is the carbon onion nanotube chain; (2) Preparing a nitrogen-doped carbon onion nanotube chain absorbing material: uniformly mixing the carbon onion nanotube chain prepared in step (1) with a nitrogen source, and heat treating at 350-400° C. for 2-4 h under a protective atmosphere to obtain a nitrogen-doped carbon onion nanotube chain absorbing material; The plate is a temperature-resistant plate with a smooth surface; The carbon onion nanotube chain has a chain length of 200-400 nm and a tube diameter of 20-50 nm; The nitrogen source is ammonium chloride, and the mass ratio of the carbon onion nanotube chain to the ammonium chloride is (1-3):(10-20).

2. The method for preparing the nitrogen-doped carbon onion nanotube chain absorbing material according to claim 1, characterized in that: The plate is any one of a glass sheet, a silicon sheet, and an aluminum sheet.

3. The method for preparing the nitrogen-doped carbon onion nanotube chain absorbing material according to claim 1, characterized in that: The mass ratio of carbon onion nanotube chain to ammonium chloride is 1:

10.

4. The nitrogen-doped carbon onion nanotube chain absorbing material prepared by the preparation method of the nitrogen-doped carbon onion nanotube chain absorbing material according to any one of claims 1 to 3.

5. Use of the nitrogen-doped carbon onion nanotube chain absorbing material according to claim 4 in electromagnetic wave absorption.